Information Science: Science about Information, Misinformation and Disinformation - Tuđman, Miroslav (Array, 2003)
Participants in interaction, particularly in interactive network media (WWW), aim to change intentions, goals, decisions and actions of other participants in communication using information as well as disinfor-mation. Criteria for differentiation among information, misinformation and disinformation are suggested based on the value of information for different participants in interaction. Therefore, the notion of rele-vance needs to be redefined and efficiency of information is analyzed from the point of view of partici-pants in the communication process. Usability of information is defined as a measure of efficiency of the information process judged by the user, while usefulness of information is a measure of sender's effi-ciency regarding the decision-making processes and actions of the information user. Usefulness is a measure of the actual effect of the author (source) of information on the choice of goals, decisions and actions of the information user.